Corporate social responsibility (CSR) disclosure and banks’ fi-nancial performance in Five ASEAN countries - Aria Farah Mita; Harry Ferdinand Silalahi; Alin Halimastussadiah (Journal of Economics, Business, and Accountancy Ventura, 2018)
The financial industry in particular the banking sector plays an important role in the economy. The Bank acts as a financial intermediary in the society. Thus, it is important that banks are well-managed and act responsibly. The concept of corporate social responsibility (CSR) is an integral concept for realizing a responsible banking practice. A responsible bank is believed that it will be more sustainable in carrying out its role as an intermediary of funds in the society. This study is preliminary work that attempts to examine the social responsibility of banks in ASEAN-5. The objective of this research is to analyze the level of CSR in commercial banks in ASEAN-5, namely Indonesia, Philippines, Malaysia, Singapore, and Thailand in 2014. This study describes the level of CSR based on the analysis of disclosure in company's report using indicators from GRI G4 Sustainability Reporting Guidelines and GRI G4 Sector Disclosures: Financial Services. This study finds that the overall score of CSR disclosure of all listed banks is low. The CSR of commercial banks in Thailand is the highest. Banks, which published separate CSR or Sustainability Report, show a higher level of CSR compared to banks which include CSR section in their Annual Report. In addition, this study finds that CSR is positively correlated with financial performance.